KONSEP AKAD MUSYAROKAH (Sebuah Telaah Keritis Penerapan Akad Musyarokah) - ADIBATUL HAFIDLAH ADIBATUL HAFIDLAH (HUMAN FALAH: Jurnal Studi Ekonomi dan Bisnis Islam, 2019)
MMQ stands for Musyarakah Mutanaqishah which is a contract where ownership of assets (goods) or capital of one party is reduced due to purchase purchases by other parties. BMT Al-Hikmah Mlonggo uses MMQ agreements on multipurpose financing since November 2018. This study aims to study MMQ financing procedures and suitability of using multipurpose Musyarakah Mutanaqishah contracts at BMT Al-Hikmah Mlonggo with National Sharia Council Fatwa NO: 73 / DSN-MUI / 2008 and Decree of the National Sharia Council - Indonesian Ulema Council No. 01 / DSN-MUI / X / 2013. This research is a qualitative research using observation, interview and documentation methods to obtain data relating to MMQ at BMT Al-Hikmah Mlonggo. Data analysis techniques are used with the stages of data reduction, model data and conclusions. Based on the results of the study, the results of this study can be concluded that BMT Al-Hikmah Mlonggo has not fully applied the musyarakah mutanaqishah agreement based on the MUI fatwa. In determining the margin of the MUI musyarakah mutanaqishah fatwa contract, the margin decision must be discussed with the requirements that must be in practice, only asking for the margin standard set by BMT Al-Hikmah Mlonggo.